Design of An Internet of Things-Based Intelligent Cutlery Cleaning Tool - Lindawati, Lindawati; Salamah, Irma; Astari, Devina (Universitas Negeri Padang, 2024)
Technology that continues to develop has given rise to many new technologies that help humans work; one example is washing dishes. Because this work is quite time-consuming, it created an automatic dishwasher based on the Internet of Things (IoT). This tool aims to build a tool that can help homemakers complete one of their homework, namely washing tableware. This research was conducted by making a prototype design using Arduino Mega 2560 and NodeMCU and supported by Android applications using the XML programming language. In the application, there are control and monitoring features. The control feature in the application will control the number of rounds of water used, while the monitoring feature is used to monitor the water discharge used during washing. In addition, this tool also uses Firebase as a database used to store data. By incorporating sensors and technology into this appliance, a more efficient, programmable, and customized washing experience is possible. The appliance underwent 27 tests, with an overall success rate of 88,89%.